The association between stock returns and foreign GAAP earnings versus earnings adjusted to U.S. GAAP - Chan, Kam C.; Seow, Gim S. (Journal of Accounting and Economics, 1996)
This study examines the association between stock returns and foreign GAAP earnings versus earnings adjusted to U.S. GAAP. Using a sample of foreign firms with common stock or American Depositary Receipt (ADR) traded in U.S. exchanges, we compare the returns-earnings relations between U.S. and foreign GAAP-based earnings. Results based on the JA test indicate that earnings based on foreign GAAP are more closely associated with contemporaneous stock returns than earnings reconciled to U.S. GAAP. We find evidence that our results may be driven by institutional factors which are specific to foreign markets.